Expression patterns of major genes in fatty acid synthesis, inflammation, oxidative stress pathways from colostrum to milk in Damascus goats - Akın Yakan (Nature Portfolio, 2021)
Abstract The molecular regulation of milk secretion and quality in the transition period from colostrum to milk in goats is largely unknown. In the present study, mammary gland secretion of goats was collected in 0th, 4th, 7th, 14th and 28th days after parturition. In addition to composition and fatty acid profile of colostrum or milk, FASN, SCD, ACACA, COX-2, NRF2, TLR2, NF-kB, LTF and PTX3 genes expression patterns were determined from milk somatic cells. While somatic cell count (SCC), malondialdehyde (MDA), fat, fat-free dry matter, protein and lactose were highest as expression levels of the oxidative and inflammatory genes, freezing point and electrical conductivity were lowest in colostrum. With the continuation of lactation, most of the fatty acids, n3 ratio, and odour index increased but C14:0 and C16:0 decreased. While FASN was upregulated almost threefolds in 14th day, ACACA was upregulated more than fivefolds in 7th and 14th days. Separately, the major genes in fatty acid synthesis, inflammation and oxidative stress were significantly associated with each other due to being positively correlated. MDA was positively correlated with SCC and some of the genes related inflammation and oxidative stress. Furthermore, significant negative correlations were determined between SCC and fatty acid synthesis related genes. With this study, transition period of mammary secretion was particularly clarified at the molecular levels in Damascus goats.